Analisis Kriminologis terhadap Kasus Pembunuhan dan Mutilasi di Ngawi: Studi Motif dan Pola Kejahatan - Lestiani, Lia; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The murder case accompanied by mutilation in Ngawi is a form of extreme crime that has shaken society. This study aims to analyze the motives and patterns of the perpetrators' crimes through a criminology approach. The study was conducted qualitatively by collecting secondary data from media reports and official documents. The findings show that the perpetrators' actions were influenced by deep emotional and personal motives, and were carried out with planning and efforts to eliminate traces. This study uses the Rational Choice, Social Learning, and Strain Theory theories to explain the perpetrators' behavior. The results show that the perpetrators were not only driven by emotions, but also considered risks and ways to avoid detection. This study is expected to contribute to the understanding and prevention of similar crimes.